Some Mechanical Properties of Dental Stone Specimens after Disinfections by 70% Hospital Sprit - Kamal, Amera (Zanco Journal of Medical Sciences (ZJMS), 2009)
Background and objective: The transmission of oral pathogens to impression and subsequently on to gypsum casts had been demonstrated. The aim of the study to investigate the effect of disinfections of type III dental stone casts by spraying and immersion in 70% hospital sprit (ethanol) on the compressive strength and surface roughness at two different time intervals (24 and 48) hours. Methods: Forty eight cylindrical stone specimens (12 for each group), were prepared for compressive strength and surface roughness testing. Six specimens of each group were tested after (24) hours and the other six after (48) hours. Results: The study showed no significant differences in values of compressive strength and surface roughness between the control and sprayed groups at (24 and 48) hours, this could be due to the fact that the sprayed specimens absorbs fewer amounts of disinfectants than the immersed groups. Conclusion: The immersion of the specimens in (70%) ethanol for (10) seconds and (30) minutes decrease the compressive strength and increase the surface roughness.